Partial Sequencing of IS1216V Transposase Gene of Staphylococcus Aureus Isolated from Food Samples - Auda, Ibtesam G. (AL-Kindy College Medical Journal, 2019)
Background:  Insertion sequence is a short DNA sequence encode for proteins implicated in the transposition activity. Transposase  catalyzes the enzymatic reaction allowing the insertion sequence  to +9*lo2 move. ;qqa;.Objective: To study the sequencing of transposase gene, tnp, IS1216V of S. aureus isolated from food and then compared with that documented in National Center for Biotechnology Information (NCBI).Methods: Food samples of animal and plant origin were collected, and screened for presence of S. aureus, IS1216V was identified in the Tn1546-like elements in the genomes of all Staphylococcus aureus isolates.Results: About 75% of total food samples were positive to S. aureus especially in the food of animal origin. tnp amplification showed that, 85% of isolates gave positive result.   Sequencing of amplified part of  IS1216V tnp of S. aureus isolates showed that,  tnp gene had high identity (78-79%) with the reference strains of NCBI.Conclusion: High percentage of  local food samples were contaminated with S. aureus especially of animal origin. Most of the S. aureus isolates showed the presence of transposase gene (tnp) of IS1216V. Sequencing showed some dissimilarity between the sequence of transposase gene (tnp) of IS1216V  S. aureus isolated from local foods and strains  recorded in database of  NCBI.